2016
DOI: 10.5933/jkapd.2016.43.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Ectopic Eruption of the Maxillary First Permanent Molar

Abstract: In order to provide a diagnostic basis for predicting the possibility of the self-correction of ectopic first permanent molars, differences among normal eruption, reversible and irreversible ectopic eruption of maxillary first permanent molars were retrospectively analyzed. The angles of the long axes and the occlusal lines between the maxillary first permanent molar and the adjacent tooth were measured by panoramic radiographs. The occlusal relationship of second primary molars was also investigated. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(62 citation statements)
references
References 10 publications
11
49
1
Order By: Relevance
“…Based on this study, between the angle of long axis and occlusal line of PFM and PSM was measured using panoramic radiograph 3,8,20 . In this study findings showed that negative vertical angles and mean values was found more in impacted PFM consistent with the results in Sun et al 8 However, the results of this study at negative horizontal angles for impacted PFM were not consistent with previous study 8 . This may be because of the many factors affecting eruption status 7,9,10 and methodological differences with Sun et al study 8 …”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Based on this study, between the angle of long axis and occlusal line of PFM and PSM was measured using panoramic radiograph 3,8,20 . In this study findings showed that negative vertical angles and mean values was found more in impacted PFM consistent with the results in Sun et al 8 However, the results of this study at negative horizontal angles for impacted PFM were not consistent with previous study 8 . This may be because of the many factors affecting eruption status 7,9,10 and methodological differences with Sun et al study 8 …”
Section: Discussionsupporting
confidence: 82%
“…Previous studies indicated that increase in negative vertical angle of PFM were significant factors of impacted ectopic eruption of the PFM. Based on this study, between the angle of long axis and occlusal line of PFM and PSM was measured using panoramic radiograph 3,8,20 . In this study findings showed that negative vertical angles and mean values was found more in impacted PFM consistent with the results in Sun et al 8 However, the results of this study at negative horizontal angles for impacted PFM were not consistent with previous study 8 .…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations